Long‐term lamivudine treatment achieves regression of advanced liver fibrosis/cirrhosis in patients with chronic hepatitis B. Issue 2 (February 2015) - Xu, Bei; Lin, Lanyi; Xu, Guoguang; Zhuang, Yan; Guo, Qing; Liu, Yunye; Wang, Hui; Zhou, Xiaqiu; Wu, Shanming; Bao, Shisan; Cai, Wei; Xie, Qing
Abstract Background and Aim Antiviral therapy is important in advanced liver fibrosis/cirrhosis with chronic hepatitis B (AdLF‐CHB) patients, but complete regression of cirrhosis remains to be the challenge. We aimed to investigate whether up to 10 years lamivudine treatment achieves liver fibrosis/cirrhosis regression in AdLF‐CHB patients. Methods Improvement of hepatic fibrosis/cirrhosis, virological response and disease progression were evaluated in 28 AdLF‐CHB patients with up to 10 years lamivudine treatment. Liver biopsy was performed in all of the 28 patients at baseline, but only 19 patients had second biopsy at year 10. Results There were 24 hepatitis B e antigen (HBeAg)‐positive and 4 HBeAg‐negative patients within the original 28 AdLF‐CHB patients. At the end of 10 years lamivudine treatment, 20 of the 24 HBeAg‐positive patients had HBeAg loss. HBeAg seroconversion was detected in 10 of these 20 HBeAg loss patients. HBsAg loss was observed in 4 of the original 28 patients. Among these four HBsAg loss patients, three had HBsAg seroconversion. All patients achieved hepatitis B virus DNA (HBV DNA) undetectable. Histopathology was evaluated between paired original and final liver biopsies among 19 patients as follows: 4/19 achieved complete liver fibrosis/cirrhosis regression; 9/19 improved in Ishak fibrosis score; whereas 6/19 showed no fibrosis improvement. About 75% patients achieved inflammatory/fibrotic improvement. No significant disease progression was observed in 24/28 patients. Furthermore, no significant difference in histopathology improvement, cirrhosis regression, disease progression between non‐resistance and rescue for resistance was observed. Conclusion Long‐term lamivudine therapy achieves regression of fibrosis/cirrhosis and improvement of histological and disease progression in AdLF‐CHB patients.